The central position of agriculture within the 2030 Agenda for Sustainable Development - Omilola, Babatunde; Robele, Sophia (International Food Policy Research Institute, 2017)
This paper provides a helpful framing to understand both why and how policy attention and investments should be channeled through agriculture and agrifood systems as key vehicles for achieving the Sustainable Development Goals (SDGs). It illustrates the ways in which agriculture, particularly within the context of food value chains, is uniquely positioned to holistically address the social, economic, and environmental dimensions of sustainable development because of its existing reach and future potential. In this paper’s examination of the multiplicity of entry points the sector offers for fostering inclusive and sustainable economic growth, reversing harmful environmental trends, and enhancing the resilience of the poorest and most vulnerable populations, it traces some of the most potent pathways for agricultural policies and interventions to accelerate development outcomes across all country contexts.